Decorating sdAbs with Chelators: Effect of Conjugation on Biodistribution and Functionality - Henri Baudhuin; Janik Puttemans; Heleen Hanssens; Philippe Vanwolleghem; Sophie Hernot; Geert Raes; Catarina Xavier; Tony Lahoutte; Pieterjan Debie (MDPI AG, 2021)
Single domain antibodies (sdAbs) have proven to be valuable probes for molecular imaging. In order to produce such probes, one strategy is the functionalization of the reactive amine side chain of lysines with a chelator, resulting in a mixture of compounds with a different degree of conjugation. In this study, we implemented anion exchange chromatography (AEX) to separate the different compounds or fractions that were further characterized and evaluated to study the impact of the conjugation degree on pharmacokinetic properties and functionality. Anti-HER2 and anti-MMR sdAbs were functionalized with NOTA or DTPA chelator. Anion exchange chromatography was performed using 0.02 mol/L Tris pH 7.5 as the first solvent and 0.25 M or 0.4 M NaCl (in case of NOTA chelator or DTPA chelator, respectively) as the second solvent applied as a gradient. The fractions were characterized via mass spectrometry (MS), surface plasmon resonance (SPR), and isoelectric focusing gel electrophoresis (IEF), while in vivo studies were performed after radiolabeling with either 68Ga (NOTA) or 111In (DTPA) to assess the impact of the conjugation degree on pharmacokinetics. AEX could successfully be applied to separate fractions of (chelator)n-anti-HER2 and (chelator)n-anti-MMR sdAb constructs. MS confirmed the identity of different peaks obtained in the separation process. SPR measurement suggests a small loss of affinity for (chelator)3-anti-sdAb, while IEF revealed a correlated decrease in isoelectric point (pI) with the number of conjugated chelators. Interestingly, both the reduction in affinity and in pI was stronger with the DTPA chelator than with NOTA for both sdAbs. In vivo data showed no significant differences in organ uptake for any construct, except for (DTPA)n-anti-MMR, which showed a significantly higher liver uptake for (DTPA)1-anti-MMR compared to (DTPA)2-anti-MMR and (DTPA)3-anti-MMR. For all constructs in general, high kidney uptake was observed, due to the typical renal clearance of sdAb-based tracers. The kidney uptake showed significant differences between fractions of a same construct and indicates that a higher conjugation degree improves kidney clearance. AEX allows the separation of sdAbs with a different degree of conjugation and provides the opportunity to further characterize individual fractions. The conjugation of a chelator to sdAbs can alter some properties of the tracers, such as pI; however, the impact on the general biodistribution profile and tumor targeting was minimal.